Digital Journalism and Revenue Sustainability of Print Media Organisations in Nigeria - Okuchemiya Success; Abdullahi Aliyu Maiwada (Britain International for Academic Research (BIAR) Publisher, 2026)
The expansion of digital technologies, internet connectivity, and smartphone usage has significantly transformed the Nigerian newspaper industry, altering traditional patterns of news production, distribution, consumption, and audience engagement. The emergence of digital newspapers has created new opportunities for media organisations to reach wider audiences and deliver timely, interactive, and multimedia content, while simultaneously posing significant economic and operational challenges to conventional print media outfits. This study examines the impact of digital newspapers on print media organisations in Nigeria, with particular attention to changes in readership patterns, revenue generation, newsroom operations, production and distribution practices, and organisational sustainability. The study adopts a qualitative research approach and relies on secondary data obtained from relevant scholarly journal articles, books, published studies, industry reports, and other documentary sources relating to digital journalism and the Nigerian newspaper industry. The data were reviewed and thematically analysed to identify major trends and patterns associated with the digital transformation of print media. Anchored on the Diffusion of Innovations Theory, the study demonstrates that digital migration has encouraged Nigerian print media organisations to adopt online platforms, multimedia production, social media engagement, audience analytics, and alternative revenue models. However, the transition has also contributed to declining print readership, reduced advertising income, rising competitive pressures, and concerns about the long-term sustainability of traditional print operations. The study concludes that the survival and relevance of print media organisations in Nigeria increasingly depend on strategic digital transformation, innovative revenue diversification, technological adaptation, and the ability to maintain journalistic credibility while responding to changing audience expectations.